Has the relationship between formal education and the formal employment sector in Nepal changed between 1995 and 2014? - Thomas Bolli; Mahesh Nath Parajuli; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2019)
This paper analyses the relationship between formal education and the formal employment sector in Nepal. The analysis of several individual-level surveys between 1995 and 2014 shows that completed teriary education increases the probability to be wage-employed in the non-agricultural sector, while primary and secondary education hat little relationship with wage-employment. However, primary, secondary and tertiary education all increase an extended measure of formal sector empoloyment that accounts for company registration and size. This highlights the relevance of choosing the appropriate measure of formal sector employment. The strength of the relationship between completed primary and secondary education and formal sector employment has decreased over time. This decrease provides suggestive implying that the informal employment sector provides relatively more opportunities in 2014 than 20 years earlier. The relationship between tertiary education and wage-employment has also decreased but the relationship between tertiary education and the extended measure of formal sector employment has remained stable. This might reflect the large share of tertiary educated working in government related sectors.
Keywords: 330